Determination of Patient Preference for Location of Elective Abdominal Aortic Aneurysm Surgery. (May 2013) - Landau, John H.; Novick, Teresa V.; Dubois, Luc; Power, Adam H.; Harris, Jeremy R.; DeRose, Guy; Forbes, Thomas L.
Objective: Aneurysm repair is centralized in higher volume centers resulting in reduced mortality, with longer travel distances. The purpose of this study is to explore patients' preference between local care versus longer distances and lower mortality rates. Methods: Patients with abdominal aortic aneurysm (AAA) measuring 4 to 5 cm and living at least a 1-hour drive from our hospital were asked to assume it had grown to 5.5 cm, and repair was recommended with a mortality risk of 2%. The level of additional risk they would accept to undergo surgery locally was determined. Results: A total of 67 patients were surveyed. If mortality risk was equivalent at the local and regional hospitals, 44% preferred care at our tertiary center, while 56% preferred surgery locally. If perioperative mortality was increased at the local hospital, 9% preferred local surgery. Conclusions: The vast majority of patients with AAA will accept longer travel distances for care as long as it results in a reduction in perioperative mortality.